Analyzing Political Distrust as a Driving Factor for Protesting Political Actions in the Context of Security Threats and Political Corruption - Mahmoudreza Rahbarqazi; Morteza Ebrahimi (Strategic Research on Social Problems)
Introduction In modern societies, political emotions and attitudes play a significant role in shaping individuals' political behaviors. Two critical factors—perceived threats and political corruption—exert both direct and indirect effects on citizen actions. Perceived threats, whether arising from external security risks or internal issues like discrimination, tend to heighten anxiety and prompt political engagement as individuals seek solutions. Conversely, political corruption undermines trust in institutions but can also galvanize citizens to advocate for systemic reforms. Political distrust acts as a crucial link, connecting perceptions of corruption and security threats to increased political participation, such as voting or protesting. This study examined the mediating role of political distrust in the relationship between perceived corruption and security threats in relation to protest behavior in Iran. By addressing this important gap in the literature, the research offered valuable insights into the dynamics of political behavior and social unrest.